Cultivated forages as climate solutions to transform livestock systems in the Global South - Arango, Jacobo; Costa Junior, Ciniro (2025)
At the FAO Global Conference on Sustainable Livestock Transformation, held in Rome on September 30, 2025, Alliance Scientist Jacobo Arango moderated the side event on 'Cultivated forages as climate solutions to transform livestock systems in the Global South': A session that explored how cultivated forages can serve as practical climate-smart solutions to transform livestock systems by improving productivity, reducing greenhouse gas emissions, enhancing soil health and strengthening resilience.